2021
DOI: 10.1029/2020gl090617
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Compound Drought and Heatwaves in a Warming World

Abstract: The evolution of drought and heatwaves are controlled by a variety of land surface fluxes (Mishra & Singh, 2010), and their spatial patterns are heterogeneous due to the regional differences in precipitation, temperature anomalies, and other hydrological changes (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
132
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(152 citation statements)
references
References 63 publications
(94 reference statements)
5
132
0
Order By: Relevance
“…Concurrent hot and dry events (CHDs) can result in significant socio-economic damages, compared to individual events (Leonard et al, 2014). The observed increase in CHDs, which severally impacted the society, economy, and the environment over the past decades, has brought the scientific community to make an extensive analysis of the variability, trends, and future projection of these events, either at global scale (Feng et al, 2020;Ridder et al, 2020;Mukherjee and Mishra, 2021) or at regional scale (Kattsov et al, 2005;Von Buttlar et al, 2018;Hao et al, 2019;Russo et al, 2019;Vogel et al, 2019;Bezak and Mikoš, 2020;Kong et al, 2020). In this respect, we explored the spatio-temporal variability of CHDs at European level and we quantified the relationship between the occurrence of CHDs and the large-scale atmospheric circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrent hot and dry events (CHDs) can result in significant socio-economic damages, compared to individual events (Leonard et al, 2014). The observed increase in CHDs, which severally impacted the society, economy, and the environment over the past decades, has brought the scientific community to make an extensive analysis of the variability, trends, and future projection of these events, either at global scale (Feng et al, 2020;Ridder et al, 2020;Mukherjee and Mishra, 2021) or at regional scale (Kattsov et al, 2005;Von Buttlar et al, 2018;Hao et al, 2019;Russo et al, 2019;Vogel et al, 2019;Bezak and Mikoš, 2020;Kong et al, 2020). In this respect, we explored the spatio-temporal variability of CHDs at European level and we quantified the relationship between the occurrence of CHDs and the large-scale atmospheric circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the global analysis using in situ observations and earth system models showed that the co‐occurrence of increased VPD and low SM is projected to be more frequent and severe under the warming climate (Zhou et al., 2019). However, a majority of the previous studies (Mukherjee & Mishra, 2020; Sharma & Mujumdar, 2017; Zhou et al., 2019; Zscheischler et al., 2018; Zscheischler & Seneviratne, 2017) on compound extremes are based on the future projections that do not account for the role of irrigation. Therefore, the risk of compound extremes in heavily irrigated regions may be under or overestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the profound implications, the role of irrigation on compound extremes of low soil moisture and high VPD has not been examined in India. Previous studies reported the mechanisms for concurrent soil moisture – VPD, heatwave – temperature, and heatwave – drought events at the global and regional scales (AghaKouchak et al., 2014; Ambika & Mishra, 2020; Mishra, Ambika, et al., 2020; Mishra, Thirumalai, et al., 2020; Mukherjee & Mishra, 2020; Sharma & Mujumdar, 2017; Zhou et al., 2019), however, the role of irrigation was not considered. For instance, compound extremes of drought and heatwaves at short and long time‐scales are attributable to anticyclone, atmospheric blocking, and advection of air masses (Zhou et al., 2019; Zscheischler et al., 2018, 2020), which can be significantly modulated by irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…Heatwaves are predicted to increase in frequency, duration and intensity as a result of climate change [ 1 ]. The formation of heatwaves can vary based on location, yet is fundamentally a result of high pressure in the upper atmosphere trapping hot, low-pressure air close to the Earth’s surface for extended periods [ 2 ].…”
Section: Introductionmentioning
confidence: 99%